Schwannoma intralaberíntico. Descripción de un caso - Cámara Arnaiz, José Antonio (2016)
Introduction and objectives: The intralabyrinthine schwannoma is a rare benign tumor, with extradural slow growth, located primarily in the membranous labyrinth. Through a clinical case, we present the characteristics of its evolution, we try to offer a physio-pathological explanation of symptoms and audio-vestibular findings and finally, we describe the therapeutic options. Description: We present a 59 year old woman, beginning with non-specific symptoms of the left ear and then concerned because of a hearing loss in that ear. To confirm that it is a non-justified unilateral hearing loss , MRI was requested and it shows the presence of a small intravestibular tumor of 2-3 mm which we will review periodically. Discussion: The origin and the prevalence of intralabyrinthine schwannomas are unknown. Even though the clinic is confused with other frequent otological processes, the implementation of MRI would increase the number of diagnosed cases. Depending on the patient, their symptoms, evolution and tumor characteristics, the type of treatment is decided. Conclusion: Intralabyrinthine schwannoma should be part of the differential diagnosis in patients with unilateral audio-vestibular symptoms and request a high resolution MRI to obtain the definitive diagnosis. Presenting an excellent prognosis, the observation is considered the best treatment option.